AB0142 Igm antibodies against phosphorylcholine promote polarization of t regulatory cells from patients with atherosclerotic plaques, systemic lupus erythematosus and healthy donors: a novel immunological concept. (15th June 2017) - Sun, J; Lundström, S; Zhang, B; Zubarev, R; Steuer, J; Gillgren, P; Rahman, M; Ajeganova, S; Liu, A; Frostegård, J
Abstract : Background: IgM antibodies against Phosphorylcholine (anti-PC) are negatively associated with atherosclerosis, cardiovascular disease (CVD) and systemic lupus erythematosus (SLE) where the risk of CVD and atherosclerosis is very high. We here study effects of IgM anti-PC on Th17 and T regulatory cells (Tregs). Objectives: Immunomodulation in atherosclerosis and SLE could have a huge impact on disease prevention and treatment. Methods: Mononuclear leukocytes were isolated from peripheral blood (PBMC) obtained from healthy blood donors, from six SLE patients with age- and sex-matched controls and from symptom-giving human atherosclerotic plaques. The proportion of Th17 (CD4 + CCR6 + ) and Treg (CD4 + CD25 + CD127 dim/- ) cells were determined by flow cytometry in CD4 + T cells after 6 days culture with Th17 or Treg-polarizing cytokines, with PMA and Ionomycin stimulation. IgM anti-PC were extracted from total IgM, with flow-through IgM as controls. Dendritic cells (DC) were differentiated from PBMC. Antibody peptide/protein characterization was done by a proteomics de novo sequencing approach. Results: IgM anti-PC increased significantly the proportion of Tregs from healthy donors, SLE patients and from atherosclerotic plaque cells while control antibodies did not. T cells from SLE patients had a significantly lower proportion of Tregs and higher proportion of Th17 cells as compared to matched controls. IgM anti-PC but not control antibodies significantly reduced production of IL-17 and TNF-alpha in cell culture from SLE patients and from atherosclerotic plaque cells. IgM anti-PC interacted with CD40 and kept DCs in an immature stage potentially being tolerogenic. We identify differences on the IgM peptide expression level in anti-PC compared to control antibodies. Conclusions: IgM anti-PC increase Tregs and having low levels could contribute to both SLE and atherosclerosis (and CVD) and could thus represent a novel underlying mechanism in these conditions. This finding could also have therapeutic implications. Disclosure of Interest: None declared